Investigating the differential impact of school and community-based integrated control programmes for soil-transmitted helminths in Timor-Leste: the (S)WASH-D for Worms pilot study protocol. Issue 1 (December 2016) - Clarke, Naomi; Clements, Archie; Bryan, Stuart; McGown, John; Gray, Darren; Nery, Susana
Abstract Background Water, sanitation and hygiene (WASH) interventions represent an important component of soil-transmitted helminth (STH) infection control, alongside the administration of anthelmintic drugs, which are generally targeted to school-aged children. Recent modelling studies have suggested that STH control programmes should be broadened to include all age groups across the community. We describe the protocol for a pilot study investigating the impact of school-versus-community-based delivery of integrated WASH and deworming programmes on STH infections in school-aged children in Timor-Leste. Methods The (S)WASH-D for Worms pilot is a two-arm, non-randomised cluster intervention study. The aims are to determine feasibility and acceptability of the intervention and study procedures and to establish proof of principle for the hypothesis that STH control programmes directed to the entire community will lead to greater reductions in STH infections in children than programmes directed only to school-aged children. Of the six participating communities, three receive a school-based integrated WASH and deworming programme and three additionally receive a community-based integrated WASH and deworming programme. The primary outcomes are the proportions of eligible children who enrol in the study and participate in the data collection, and outcomes relating to WASH and deworming programme completion, coverage, and use. Secondary outcomes are the cumulative incidence and mean intensity of STH infection in school-aged children at 6-month follow-up, mean haemoglobin concentration and several anthropometric indices. Results will inform the design of a cluster-randomised controlled trial (RCT). Discussion This pilot study is being conducted in preparation for a cluster-RCT investigating the differential impact of school- and community-based integrated STH control programmes on STH infections in school-aged children. It aims to establish feasibility and proof of principle, while results of the subsequent RCT could have significant implications for global STH control policy. Trial registration Australian New Zealand Clinical Trials Registry, ACTRN12615001012561